The Influence of Price and Brand Loyalty on Store Brands Versus National Brands - Cataluna, F.; García, A.; Phau, Ian (Routledge Taylor & Francis Group, 2006)
This article investigates how price and brand loyalty of three frequently purchased product categories can influence the purchase decision process of store brands versus national brands. A multinomial logit model was constructed to analyse the data obtained from a consumer panel. The results confirmed that brand loyalty is the main variable which influences the purchase decision process of both national and store brands. The influence of price on the purchase decision process is product specific. There is a clear distinction between the buyer's profile of store brands and national brands. But there is no evidence of any correlation between demographic variables and national brands or store brands.